The British Labour Party and the antisemitism crisis: Jeremy Corbyn and image repair theory. (November 2021) - Heppell, Timothy
This article utilises the work of William Benoit on image repair theory as a framework for examining the crisis communication of Jeremy Corbyn in relation to antisemitism within the Labour Party. By examining the self-defence rhetoric of Corbyn on the antisemitism allegations, the article identifies the following. Of the five strategies for crisis communication, Corbyn was overly reliant on denial, evading responsibility and reducing offensiveness ; struggled to explain his attempts at corrective action ; and reverted to accepting responsibility – that is, apologies – reluctantly and belatedly. Utilising existing perspectives on the most effective strategies for image repair – which emphasise the importance of effective corrective action and accepting responsibility at the expense of denial, evading responsibility and reducing effectiveness – the article argues that Corbyn undermined his own attempts at image repair in the crisis that defined his leadership.